2020
DOI: 10.1002/mrd.23335
|View full text |Cite
|
Sign up to set email alerts
|

Generation of viable PDX1 gene‐edited founder pigs as providers of nonmosaics

Abstract: Pancreatic duodenal homeobox 1 (PDX1) is a crucial gene for pancreas development during the fetal period. PDX1-modified pigs have the potential to be used as a model of diabetes mellitus. However, the severe health problems caused by the PDX1 mutation limit phenotypic studies of PDX1-modified pigs as diabetes models. In this study, we generated PDX1-modified pigs by the CRISPR/Cas9 system introduced into zygotes via electroporation and investigated the mosaicism, phenotypes, and inheritance of the resulting pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…We observed that the piglet harbored mutations, as observed in the ear biopsy analysis, in its major organs at various frequencies. Our previous study demonstrated mosaicism of major organs with frequencies similar to those observed in the results of the ear biopsy analysis [35]. The frequency of genotype varies with organ in genetically modified F0 pigs, indicating that a careful observation of WT sequence/in-frame mutation in the genomic DNA is an essential step to apply these organs for transplantation.…”
Section: Discussionsupporting
confidence: 64%
“…We observed that the piglet harbored mutations, as observed in the ear biopsy analysis, in its major organs at various frequencies. Our previous study demonstrated mosaicism of major organs with frequencies similar to those observed in the results of the ear biopsy analysis [35]. The frequency of genotype varies with organ in genetically modified F0 pigs, indicating that a careful observation of WT sequence/in-frame mutation in the genomic DNA is an essential step to apply these organs for transplantation.…”
Section: Discussionsupporting
confidence: 64%
“…In mice, electroporation is widely used to introduce gene editors [ 51 ]. Gene editing via electroporation has also been applied to porcine zygotes [ 52 ], with successful gene modification (knockout) [ 52 , 53 , 54 , 55 ]. Electroporation-mediated gene editing requires no specialized equipment and benefits from a simple process and high zygote viability.…”
Section: Methods For Generation Of Genetically Modified Pigs Using Gene Editorsmentioning
confidence: 99%
“…(2019) [ 107 ] PDX1 EP CRISPR Tanihara et al . (2020) [ 54 ] Duchenne muscular dystrophy DMD CMI CRISPR Yu et al . (2016) [ 130 ] Familial hypercholesterolemia LDLR SCNT TALEN Carlson et al .…”
Section: Recent Trends In Gene Editing In Pigsmentioning
confidence: 99%
“…In contrast, pigs with low mutation rates were healthy. 37 In our preliminary trial, we realized that 20-30 copies of the Pdx1-Hes1 transgene in midgestational Pathophysiology/complications fetuses resulted in anomalies in organs, including anal atresia. As shown by our qPCR results, endogenous expression of Pdx1 on day one after birth resulted in a 30% reduction in expression compared with that in the WT group.…”
Section: Pdx1-hes1mentioning
confidence: 98%